The arene–alkene photocycloaddition - Streit, Ursula; Bochet, Christian G. (Beilstein Journal of Organic Chemistry, 2011)
In the presence of an alkene, three different modes of photocycloaddition with benzene derivatives can occur; the [2 + 2] or ortho, the [3 + 2] or meta, and the [4 + 2] or para photocycloaddition. This short review aims to demonstrate the synthetic power of these photocycloadditions.
Keywords: benzene derivatives; cycloadditions; Diels–Alder; photochemistry